Analisa Tingkat Kepuasan Masyarakat Terhadap Pelayanan Pengadilan Agama Pematangsiantar Menggunakan Algoritma C4.5 - Eka Satria Pribadi; P Poningsih; Heru Satria Tambunan (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2020)
The purpose of this study was to determine how much the level of community satisfaction with services in the Pematangsiantar Religious Court. In this study, researchers used the data mining technique C.45 algorithm. The source of research data used is by giving questionnaires to the community. In this case the researchers used the assessment attributes, among others: Service, ability, behavior, cost, and infrastructure. In this study the alternative used as a sample is Pematangsiantar City Community. the results of this study will become input for the Pematangsiantar Religious Court to provide the best possible service so that the community is satisfied with the service.